Wrongful convictions in asian countries: A systematic literature review - Le, Lan Chi (International journal of comparative and applied criminal justice, 2024)
Any wrongful conviction causes severe violations to the individual, their loved ones, the criminal justice system, and the validity of justice. While Anglo-American countries have focused on wrongful convictions since the 1930s, some Asian contexts have only considered these unjust errors within the scope of their legal approaches since the 2010s. To investigate this issue, this paper conducted a systematic literature review (SLR) of the Scopus and Google Scholar databases, collecting 36 English peer-reviewed articles from 710 publications between 2010 and 2021. Our two primary goals include: 1) reviewing the scope and response of Asian countries to wrongful convictions and 2) identifying the main factors that led to these wrongful convictions. Findings indicate that almost all publications have focused on China and Japan as representatives of Eastern Asia. Very few studies discussed other Asian areas. Alongside five similarities with Western societies, such as 1) false confessions, 2) torture, 3) misconduct, 4) eyewitness identification errors, and 5) misused forensic science, political factors and criminal justice struggles reflect the unique issues underpinning Asia’s wrongful convictions. Ultimately, our study calls for broader future research of a greater range of Asian countries.